A Review of the Literature on Participatory Approaches to Local Development for an Evaluation of the Effectiveness of World Bank Support for Community-Based and Driven Development Approaches - Pozzoni, Barbara; Kumar, Nalini (World Bank, Washington, DC, 2014)
This paper explores the available literature on participatory approaches to development as an input to the operations evaluation department (OED) evaluation of World Bank-supported community-based development (CBD) and community-driven development (CDD) interventions. Participatory approaches to development have gained substantial support in the international community over the past quarter century, and have become increasingly important in the work of the World Bank and other donors. Undertaking this literature review has been a particularly challenging exercise for two reasons. The Bank categories CDD approaches in a three-fold typology, which encompasses both community participation efforts and participatory governance initiatives. This paper is primarily concerned with regularized participatory spaces, in which community members deliberate over the provision of services and the allocation of resources, rather than transient spaces, which entail one-off events or exercises aimed at generating discussion on specific policy issues with no direct link to decision making. This review was undertaken with a four-fold objective. First, to simply bring to the ongoing CBD and CDD evaluation information on the kind of evidence that is out on participatory approaches to local development, qualitative, quantitative, and anecdotal. Second, to draw on the evidence in the literature to understand the different kinds of participatory spaces that Bank's CBD and CDD interventions have fostered at the local level. Third, to explore the evidence in the literature on factors that has a bearing on development effectiveness of CBD and CDD-type interventions. Finally, to provide a means for testing the findings emerging from other study components, particularly case study countries and the portfolio review both of which indicate several challenges that donor agencies face in implementing participatory projects. This review proceeds in six sections. Section one gives introduction; section two examines the evidence in the literature on the extent to which participation in decision-making has promoted inclusiveness; section three explores factors that are likely to facilitate or hinder participatory and collective undertakings; section four assesses the development effectiveness of participatory interventions; section five explores key issues related to the institutional contexts of CBD and CDD-type interventions; and finally section six draws on the evidence in the literature to explore the main challenges that donors and lenders are likely to encounter in the promotion of the CDD approach.